A Fully Conjugated TTF-π-TCAQ System: Synthesis, Structure, and Electronic Properties - Santos, Jose; Illescas, Beatriz M.; Martin, Nazario; Adrio, Javier; Carretero, Juan C.; Viruela, Rafael; Orti, Enrique; Spänig, Fabian; Guldi, Dirk Michael (Chemistry - A European Journal, 2011)
The synthesis of the first fully conjugated tetrathiafulvalene–tetracyano-p-quinodimethane ((TTF)–TCNQ)-type system has been carried out by means of a Julia–Kocienski olefination reaction. In particular, a tetracyanoanthraquinodimethane (TCAQ) formyl derivative and two new sulfonylmethyl-exTTFs (exTTF=2-[9-(1,3-dithiol-2-ylidene)anthracen-10(9H)-ylidene]-1,3-dithiole)—prepared as new building blocks—were linked. A variety of experimental conditions reveal that the use of sodium hexamethyldisilazane (NaHMDS) as base in THF afforded the E olefins with excellent stereoselectivity. Theoretical calculations at the B3LYP/6-31G** level point to highly distorted exTTF and TCAQ that form an almost planar stilbene unit between them. Although calculations predicted appreciable electronic communication between the donor and the acceptor, cyclic voltammetric studies did not substantiate this effect. It was only in photophysical assays that the electronic communication emerged in the form of a charge-transfer (CT) absorption and emission. Once photoexcited (i.e., the locally excited state or excited charge-transfer state), an ultrafast, subpicosecond charge separation leads to a radical ion pair state in which the spectroscopic features of the radical cation of exTTF as well as the radical anion of TCAQ are discernable. The radical ion pair is metastable and undergoes a fast ((1.0±0.2)ps) charge recombination to reconstitute the electronic ground state. Such ultrafast charge separation and recombination processes come as a consequence of the very short vinyl linkage between the two electroactive units.
EAM Import::2019-03-13